A droplet digital PCR assay for detection and quantification of Verticillium nonalfalfae and V. albo-atrum - Wang, Di; Liu, Enliang; Liu, Haiyang; Jin, Xi; Niu, Chunyan; Gao, Yunhua; Su, Xiaofeng (Frontiers in Cellular and Infection Microbiology, 2023)
Verticillium nonalfalfae and V. albo-atrum are notorious pathogenic fungi that cause a destructive vascular disease called Verticillium wilt worldwide. Thus, timely and quantitative monitoring of fungal progression is highly desirable for early diagnosis and risk assessment. In this study, we developed a droplet digital polymerase chain reaction (ddPCR) assay to detect and quantify V. nonalfalfae and V. albo-atrum. The performance of this assay was validated in comparison with that of a quantitative real-time polymerase chain reaction (qPCR) assay. The standard curve analysis of the ddPCR assay showed good linearity. The ddPCR assay indicated similar detection sensitivity to that of qPCR on pure genomic DNA, while it enhanced the positive rate for low-abundance fungi, especially in alfalfa stems. Receiver operating characteristic analysis revealed that ddPCR provided superior diagnostic performance on field tissues compared to qPCR, and the area under curve values were 0.94 and 0.90 for alfalfa roots and stems, respectively. Additionally, the quantitative results of the two methods were highly concordant (roots: R2 = 0.91; stems: R2 = 0.76); however, the concentrations determined by ddPCR were generally higher than those determined by qPCR. This discrepancy was potentially caused by differing amplification efficiencies for qPCR between cultured and field samples. Furthermore, the ddPCR assays appreciably improved quantitative precision, as reflected by lower coefficients of variation. Overall, the ddPCR method enables sensitive detection and accurate quantification of V. nonalfalfae and V. albo-atrum, providing a valuable tool for evaluating disease progression and enacting effective disease control.